Checklist of the vascular plants of the Cantabrian Mountains - Borja Jiménez-Alfaro; Luis Carlón; Eduardo Fernández-Pascual; Carmen Acedo; Estrella Alfaro-Saiz; Raquel Alonso Redondo; Eduardo Cires; Fermín del Egido Mazuelas; Sara del Río; Tomas E Díaz Gonz´alez; Marta Eva García González; Carmen Lence; et al. (Mediterranean Botany, 2021)
We present the first standardized list of the vascular flora of the Cantabrian Mountains, a transitional zone between the Eurosiberian and Mediterranean biogeographic regions in northwestern Spain. The study area comprises 15000 km2 divided in UTM grid cells of 10 km x 10 km, for which we revised occurrence data reported in the Spanish Plant Information System (Anthos) and the online database of Iberian and Macaronesian Vegetation (SIVIM). We used a semi-automatic procedure to standardize taxonomic concepts into a single list of names, which was further updated by expert-based revision with the support of national and regional literature. In the current version, the checklist of the Cantabrian Mountains contains 2338 native species and subspecies, from which 56 are endemic to the study area. The nomenclature of the checklist follows Euro+Med in 97% of taxa, including annotations when other criteria has been used and for taxa with uncertain status. We also provide a list of 492 non-native taxa that were erroneously reported in the study area, a list of local apomictic taxa, a phylogenetic tree linked to The Plant List, a standardized calculation of Ellenberg Ecological Indicator Values for 80% of the flora, and information about life forms, IUCN threat categories and legal protection status. Our review demonstrates how the Cantabrian mountains represent a key floristic region in southern Europe and a relevant phytogeographical hub in south-western Europe. The checklist and all related information are freely accessible in a digital repository for further uses in basic and applied research